The Relationship Between Big Five Personality Factors and Mother’s Parenting Style - Isnaeni Marhani; Felicia Felicia; Kelly Santana (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
This study aims to discover a significant relationship between the Big Five personality factors owned by mothers to the type of parenting style applied by the mother, and how the relationship between the authoritative parenting type to each of the Big Five personality factors of the mother. The sampling technique is a non-probability quota type. The initial sample consisted of 349 housewives who have children in elementary and/or junior high school at National Plus schools in Jakarta. The measuring instruments used are: (1) International Personality Item Pool with a Cronbach's alpha reliability value of 0.970 to measure the Big Five personality factors, and (2) The Child Rearing Practices Report with a Cronbach's alpha reliability value of 0.992 to measure parenting style. The correlation test between the Big Five personality and mother's parenting style used Chi-Square with the result of X2 = 53.367. The Chi-Square correlation test between the agreement dimension and the authoritative parenting style had the highest percentage, which is 5.7%. The results of the correlation test showed that (1) there is a significant relationship between the Big Five personality factors and parenting style, and (2) the majority of mothers with an authoritative parenting style showed high agreement compared to other parenting styles.